Функціонування ферментів антиоксидантного захисту в клітинах слизової оболонки шлунка за умов виразкової патології при введенні омепразолу - Кот, Л.І.; Богданова, О.В.; Рахметов, А.Д.; Остапченко, Л.І. (Видавничий дім "Академперіодика" НАН України, 2008)
Superoxide dismutase, catalase, glutathione peroxidase activities in stomach mucosa cells in rats are evaluated with an experimental stress model of ulcer development and healing during five days. These parameters are also investigated under omeprazole treatment. It is established that the mucosa regeneration process is accompanied by superoxide dismutase activation and inhibition of glutathione peroxidase activity. Omeprazole treatment induced a prompt increase of the superoxide dismutase activity and a decrease of the catalase and glutathione peroxidase activities. Under conditions of omeprazole injections of unstressed rats, the superoxide dismutase activity was not changed. The inhibition of the catalase and glutathione peroxidase activities after drug treatment is observed.